Patógenos bacterianos y su incidencia en la neumonía comunitaria en pacientes de 50 a 65 años en la Parroquia Barreiro Babahoyo. Diciembre 2022- mayo 2023. - Ávila Posligua, Yalitza Lisbeth (2023)
Community pneumonia is a respiratory etiology caused by microorganisms that imply the patient's health status, evidencing said disease through symptoms and signs such as fever, dyspnea, tachycardia, among others. It is known that community pneumonia is a pathology of the respiratory system that can cause the death of the patient since it presents as an infection in the lung parenchyma with inflammation. This study was developed with the purpose of determining the incidence of community pneumonia in patients between 50 and 65 years of age in the Barreiro-Babahoyo Parish. The methodology used was deductive and analytical. In the data collection, the technique was applied through the survey directly to 100% of patients of the population of the Barreiro-Babahoyo Parish, in which it was determined that 6% of patients had the symptom of fever, 20% of patients stated that it was dyspnea, 10% of patients said that it was purulent sputum, 16% of patients mentioned that it was chest pain, 10% of patients indicated that it was tachypnoea, 10% of patients expressed that it was cough , 20% of patients pointed out that it was crackling wheezing and finally 8% of patients determined that it was dehydration. It is important to avoid risk factors such as alcohol, environmental factors and host factors (other diseases), taking into account a primary factor that is age.